Efektivitas Model Pembelajaran CPS Berbantuan LKPD Dalam MeningkatkanKemampuan Pemecahan Masalah di MTsN 3 Surabaya - Herdita Putri, Krishela; Maduri, Devi Indah; Mukarromah, Sa’ida Umi; Indayati, Tatik; Indiarti (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2024)
The purpose of this study was to determine the implementation and effectiveness of the Creative Problem Solving (CPS) learning model in improving students' problem-solving abilities in Ecology material for Grade VII. The research method used was an experiment with a quantitative research approach and also used a one-group pretest-posttest design. Data collection was carried out using observation sheets, pre-tests and post-tests. The validity test of the instrument used validity and reliability tests, normality tests, homogeneity tests, and T tests. The research findings showed that the CPS learning model was effective in improving students' problem-solving capacity in the ecology curriculum for grade VII. This was due to a significant difference between the pre-test and post-test scores, where the post-test scores were higher than the pre-test scores. Based on the research findings, it is recommended that the CPS learning paradigm be used in learning.